An extended genotyping framework for Salmonella enterica serovar Typhi, the cause of human typhoid. - Wong, V; Baker, S; Connor, T; Pickard, D; Page, A; Dave, J; Murphy, N; Holliman, R; Sefton, A; Millar, M; Dyson, Z; Dougan, G; et al. (Nature Publishing Group, 2016)
The population ofSalmonella entericaserovar Typhi (S.Typhi), the causative agent of typhoid fever, exhibits limited DNA sequence variation, which complicates efforts to rationally discriminate individual isolates. Here we utilize data from whole-genome sequences (WGS) of nearly 2,000 isolates sourced from over 60 countries to generate a robust genotyping scheme that is phylogenetically informative and compatible with a range of assays. These data show that, with the exception of the rapidly disseminating H58 subclade (now designated genotype 4.3.1), the global S. Typhi population is highly structured and includes dozens of subclades that display geographical restriction. The genotyping approach presented here can be used to interrogate localS.Typhi populations and help identify recent introductions of S. Typhi into new or previously endemic locations, providing information on their likely geographical source. This approach can be used to classify clinical isolates and provides a universal framework for further experimental investigations.